PENGGUNAAN MODEL PEMBELAJARAN WORD SQUARE UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN IPS KELAS IV SD NEGERI 012 BANGKO SEMPURNA KECAMATAN BANGKO PUSAKO KABUPATEN ROKAN HILIR - Wahyuni, Lisna; Indrawati, Henny; Haryana, Gani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract. This classroom action research, conducted in the fourth grade primary school 012 Perfect Bangko Bangko Pusako District of School Year 2015/2016. The study began on January 11 to February 1, 2016. The number of students 30 students, consisting of 15 female students and 15 male students. Based on the results of the study, an increase in teacher activity occurs on the implementation of the second cycle, which reached the percentage of 94% in the category of very perfect. From the results of observations conducted by the observer on the second cycle, the teacher has been carrying out all activities very well in accordance with the steps - steps learning word square Along with the increased activity of teachers in the second cycle, the student activity also increased reaching the percentage of 94% in the category of very high motivation learning students also appeared to increase, as seen in the first cycle only reaches the percentage of 51% in the high category, increased in the second cycle to 87% in the very high category. Based on the results of these discussions show that by using the word square models are applied in teaching, can give students motivation sehinnga learning materials delivered to attract the attention of students. Based on data analysis and discussion, the implementation of this study can be concluded that the use of square word learning model can improve students' motivation in social studies class IV Elementary School 012 Perfect Bangko Bangko Pusako District of Rokan Hilir Lesson year 2015/2016.Keywords: Word Square and Motivation